Exploring oral candidiasis among cancer patients undergoing chemotherapy in eastern Iran - Abdol Sattar Pagheh; Fatemeh Kardan; Aynaz Ghojoghi; Ahmad Reza Sebzari; Maryam Erfaninejad; Parvin Askari; Seyed Reza Aghili; Eisa Nazar; Masood Ziaee (Iranian Journal of Microbiology)
Background and Objectives: Understanding the epidemiology of Candida species among cancer patients is crucial for preventing invasive infections. This study aimed to identify Candida species and assess risk factors among cancer patients receiving chemotherapy in Birjand, eastern Iran. Materials and Methods: The samples were obtained from the oral cavity of 140 patients and the initial identification of Candida species was carried out through fungal cultures. Subsequently, Candida isolates were molecularly identified using the PCR-RFLP method with the restriction enzyme Msp1. Furthermore, the demographic characteristics, risk factors, and clinical history of the patients were extracted and scrutinized using a multiple logistic regression model. Results: Among the 140 patients examined, 55 individuals (39.3%) tested positive for oral candidiasis (OC). Notably, Hemorrhagic cancer emerged as the most common type of cancer associated with OC (46.7%). The predominant species isolated was the Candida albicans complex (64.8%), followed by the Candida glabrata complex (26.8%). A noteworthy finding was the significant association between the occurrence of OC and the number of chemotherapy sessions (P<0.05). Conversely, no significant correlations were detected between OC and variables such as sex, age, type of cancer, occupation, residence, underlying disease, and drug use (P>0.05). Conclusion: The prevalence of Candida spp. and its correlation with the number of chemotherapy sessions underscored the importance of preventive measures. These findings provided valuable insights for designing targeted interventions to mitigate the burden of oral candidiasis in this vulnerable population.